“Shakespeare’s Plausible Community: The First Act of Titus Andronicus and its Kydian Precedent” - Jordi Coral Escolà (Miscelánea: A Journal of English and American Studies, 2009)
This article re-examines the relationship between Thomas Kyd’s The Spanish Tragedy and Shakespeare’s Titus Andronicus. In the past decades the original credit of these two revenge plays of the 1590s has been restored. However, their parallel rediscovery has obscured the originality of Shakespeare’s first tragedy, which is often presented as an inferior derivative of The Spanish Tragedy. As a result, the historical significance of Shakespeare’s new representation of the self in the community has been insufficiently recognized. Shakespeare assimilated the Kydian discovery of character as the product of interactive dramatic context and developed the representation of the social basis of individual identity, an identity that grows even as it reveals itself in dialogical action. The tragic expression of this revolutionary conception of selfhood is revenge. In this perspective, Titus Andronicus ceases to appear as imitative melodrama and becomes a play that reinvents tragedy for the English Renaissance.